LOCUS OF CONTROL MODEMING INTELLECTUAL, EMOTIONAL, AND SPIRITUAL INTELLECTUAL INTELLIGENCE IN ETHICS DECISION TAX CONSULTANT - Pratama, I Made Indra; Wirama, Dewa (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.02.TAHUN 2018DO - 10.24843/EEB.2018.v07.i02.p02, 2018)
This study aims to examine the influence of intellectual, emotional, and spiritual intelligence on ethical decisions of tax consultants with locus of control as a moderating variable. The research population is all tax consultants who work at tax consultancy office in Bali area. The sample of research is determined by using purposive sampling method, the criterion used is a tax consultant who has at least one certificate brevet. Data analysis technique used in this research is multiple linear regression analysis and moderates regression analysis. The test results prove that intellectual intelligence variables affect the ethical decisions, e motional intelligence affects ethical decisions, s piritual intelligence influences ethical decisions. Locus of controlmoderate the influence intellectual intelligence, emotional intelligence, and spiritual intelligence on ethical decisions .